1991
DOI: 10.1143/jjap.30.l1110
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology of Tl2Ba2Ca2Cu3Oy Thin Films Prepared by Thallium Diffusion Process

Abstract: Restrictions on magnetic diagnostics are discussed. Being related to the integral nature of the measurable quantities, these follow from the fundamental laws of electromagnetism. A series of examples demonstrating the strength of these restrictions is analysed. The general rule is emphasized that information obtained from external magnetic measurements is insufficient for reliable evaluation of plasma current and pressure profiles in tokamaks and in stellarators. The underlying reason is that outside the plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These films have been prepared exclusively using ex situ postdeposition thallination processes, during which a precursor film is converted to the crystalline Tl 2 Ba 2 Ca 2 Cu 3 O 10 phase in the presence of a thallous oxide overpressure. 19,20,29,31,[33][34][35] A few studies have used a thallium oxide source held at a lower temperature than that of the film to maintain a thallous oxide overpressure. [34][35][36] The thallination step is most often carried out in the presence of a TlBaCaCuO powder, within a sealed gold pouch or ceramic ampoule, 21,[24][25][26][27][28] or within a closed, but unsealed, platinum or ceramic container.…”
Section: Introductionmentioning
confidence: 99%
“…These films have been prepared exclusively using ex situ postdeposition thallination processes, during which a precursor film is converted to the crystalline Tl 2 Ba 2 Ca 2 Cu 3 O 10 phase in the presence of a thallous oxide overpressure. 19,20,29,31,[33][34][35] A few studies have used a thallium oxide source held at a lower temperature than that of the film to maintain a thallous oxide overpressure. [34][35][36] The thallination step is most often carried out in the presence of a TlBaCaCuO powder, within a sealed gold pouch or ceramic ampoule, 21,[24][25][26][27][28] or within a closed, but unsealed, platinum or ceramic container.…”
Section: Introductionmentioning
confidence: 99%
“…Thallium-based thin superconducting films are considered to be very promising materials for the fabrication of various passive microelectronic devices (bandfilters, resonators, etc) due to their high critical temperature, T c , high critical current density, j c , and particularly low surface impedance at 77 K [1]. These features have been the motivation for the exploration of various methods of film fabrication such as RF sputtering [2,3], e-beam evaporation [4], thermal evaporation [5] and laser ablation [6,7]. The last method seems to be the most attractive, in that it enables one to deposit a ∼ 0.3-0.5 µm thick film in a short time (∼ 10-15 min) which is at least a factor of 10 shorter than the time needed for other methods (for example RF sputtering).…”
Section: Introductionmentioning
confidence: 99%
“…The ex situ thalliation process is thus necessary. In this process a precursor Ba 2 Ca 2 Cu 2 O x films is placed together with a Tl-rich source in an enclosure and Tl annealed at elevated temperature (700-900 • C) for a specific time, in order to increase the content of Tl in the film and to stabilize the film's properties [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has been suggested [20] that high-quality Tl-2223 films could be formed through an entirely solid-state route. Although most investigators empirically found that the processing of Tl-2212-free ceramics [10,12,[21][22][23][24][25][26][27] and films [28][29][30][31][32][33][34][35][36][37] required sintering or annealing temperatures above 850 • C, it has been shown by Lee and coworkers [38,39] that these temperatures could be lowered below 830 • C by operating in reduced oxygen partial pressures (0.03-0.15 atm). This result suggests that the amount of intermediate liquid phase might be considerably reduced by optimizing the processing parameters.…”
Section: Introductionmentioning
confidence: 99%